(untitled) (Medico Legal Update, 2020)
Background: Besides providing treatment to patients in medico legal cases, a competent medical practitioner is legally bound to collect all necessary evidence material from the body of patients which may help in the investigation of the crime and to aid in the court of law towards justice. In India, the current practice of theoretical teaching of students in Forensic Medicine towards handling medicolegal cases is not enough to deliver clinical skills effectively in handling medico-legal cases. Aims & Objectives: This study was undertaken with objectives to evaluate students perception on Clinical Forensic Medicine and impart them a hands on training towards handling antemortem medico legal cases. Material & Method: It was an educational interventional study, including 125 second MBBS undergraduate students. At the end of module, the students’ responses towards educational project on Clinical Forensic Medicine were collected in the form of a pre-validated questionnaire template. Results & Conclusion: About 52 % students responded as agreed and 29 % strongly agreed with the questionnaires at the end of this module. Students favoured Clinical Forensic Medicine Module as an effective teaching/learning method to learn on the basics of handling medico legal cases.